Impact of immunoglobulin G2 subclass level on late‐onset bacterial infection after allogeneic hematopoietic stem cell transplantation. Issue 3 (16th April 2019) - Yamazaki, Rie; Kato, Jun; Koda, Yuya; Sakurai, Masatoshi; Tozawa, Keiichi; Okayama, Mikio; Nakayama, Hitomi; Watanuki, Shintaro; Kikuchi, Taku; Hasegawa, Naoki; Okamoto, Shinichiro; Mori, Takehiko
Abstract: Background: Immunoglobulin (Ig) G2 subclass deficiency is known to be associated with recurrent bacterial respiratory infections caused by capsulated bacteria and is found mostly in pediatric patients. However, its impact after allogeneic hematopoietic stem cell transplantation (HSCT) has not been fully assessed. Methods: We retrospectively evaluated the relationship between IgG2 subclass levels and bacterial pneumonia in 74 adult patients who survived longer than 2 years after allogeneic HSCT. Results: During the evaluation period, nine patients developed bacterial pneumonia. The median IgG2 level was significantly lower in patients with an infectious episode than in those without (143 mg/dL vs 287 mg/dL; P < 0.01). In multivariate analysis, a history of rituximab therapy and cord blood as a stem cell source were significantly associated with decreased levels of both IgG2 and IgG2/IgG ratios ( P < 0.05). Conclusions: Suboptimal serum IgG2 levels could increase susceptibility to late‐onset bacterial pneumonia after allogeneic HSCT. IgG2 levels should be considered carefully, especially in patients receiving cord blood transplantation and/or rituximab treatment.